Picturing the workers' Olympics and the Spartakiads : modernist and avant-garde engagement with sport in Central Europe and the USSR, 1920-1932 /: modernist and avant-garde engagement with sport in Central Europe and the USSR, 1920-1932. (2022) - Strożek, Przemysław, 1983-
No abstract available